Encrucijadas culturales y lingüísticas en la creación del español científico-técnico - Kobiela-Kwaśniewska, Marta (Neophilologica, 2012)
The aim of the study is to present a diachronic analysis of a process of word formation in scientific and technical Spanish that is a result of many cross-cultural and linguistic influences proceeded from different linguistic communities (Iberian, Jewish, Andalusian Moors) and from the heritage of Ancient Greek and Roman. The former one is especially present in a great number of medical terms while the second one, both with English, is noticed in technical disciplines (construction, metallurgy, textile industry). Moreover, other European languages like French and Italian had an influence on the development of scientific and technical Spanish vocabulary. We also consider the main role of English, as lingua franca, in present day scientific communication, because so called anglicisms are commonly used in technical and scientific Spanish.